2019
DOI: 10.1002/clc.23252
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for improving use of evidence‐based therapy in patients with type 2 diabetes and cardiovascular disease

Abstract: Evidence‐based therapy that target hyperlipidemia, hypertension, smoking cessation, and weight loss have demonstrated significant benefits in reducing cardiovascular risks and related events. Although the benefit of intensively lowering blood glucose is unclear, newer antidiabetic drugs (glucagon‐like peptide‐1 receptor agonists and sodium‐glucose cotransporter‐2 inhibitors) have shown cardiovascular benefits in addition to their antihyperglycemic effect. Yet, studies suggest that recent use of evidence‐based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
0
8
0
1
Order By: Relevance
“…Multifaceted strategies, such as CCDS systems in combination with continuing education and feedback mechanisms, are probably more appropriate in Belgian family medicine at the moment [36,37]. Studies have already demonstrated the benefits of adding patient-oriented strategies to decision support [12,[38][39][40].…”
Section: Interpretation Of Main Resultsmentioning
confidence: 99%
“…Multifaceted strategies, such as CCDS systems in combination with continuing education and feedback mechanisms, are probably more appropriate in Belgian family medicine at the moment [36,37]. Studies have already demonstrated the benefits of adding patient-oriented strategies to decision support [12,[38][39][40].…”
Section: Interpretation Of Main Resultsmentioning
confidence: 99%
“…The practical intent of risk prediction models is to identify high risk patients such that cost‐efficient provision of advanced management strategies (eg, a novel, efficacious, yet expensive pharmaceutical) can be directed toward those patients most likely to experience untoward events, thus minimizing the number needed to treat for benefit . Ultimately, a prediction model's quantitative output implicitly proposes an action (or not) by separating “high (enough) risk” (take action) from “not high (enough) risk” (do not take action) patients.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 The practical intent of risk prediction models is to identify high risk patients such that cost-efficient provision of advanced management strategies (eg, a novel, efficacious, yet expensive pharmaceutical) can be directed toward those patients most likely to experience untoward events, thus minimizing the number needed to treat for benefit. 30 Ultimately, a prediction model's quantitative output implicitly proposes an action (or not) by separating "high (enough) risk" (take action) from "not high (enough) risk" (do not take action) patients. The current study is the first to our knowledge to propose such an objective "high risk" threshold for HHF among type 2 diabetics: a >5% probability of HHF within the next five years-reflecting the 10% highest risk patients according to model predictors.…”
Section: Discussionmentioning
confidence: 99%
“…8 Nonadherence can be unintentional; patients may forget to take medications, forget to refill a prescription, or may not take a medication correctly. 9 However, some patients may intentionally choose to not adhere to treatment due to lack of motivation or autonomy, adverse side effects, desire for control, or perceived stigmas associated with taking medication. 10 These issues may be exacerbated for patients requiring polypharmacy (40-50% of elderly patients in high-income countries) where >25% of elderly patients have a chronic intake of 10+ medicines.…”
Section: Introductionmentioning
confidence: 99%